LIVING QURAN AND SUNNAH AS THE FOUNDATION OF A HOLISTIC HEALTHY LIFESTYLE - Muhammad Faishal Hibban (International Journal of Islamic and Complementary Medicine, 2022)
Recently, health issues have indeed become an increasingly worrying discussion. Non-communicable diseases (NCDs) were a major public health challenge globally in the twenty-first century. If pulled from conditions in Indonesia, the Ministry of Health of the Republic of Indonesia shows that the prevalence of non-communicable diseases in 2018 has increased when compared to Riskesdas 2013, including cancer, stroke, chronic kidney disease, diabetes mellitus, and hypertension. It can happen due to an unhealthy lifestyle. Lifestyle changes must be made. for Islam sees health as a condition in which man is able to maintain a just attitude towards his fitrah. In solving these problems, as Muslims, they must follow the lifestyle in the Qur'an and sunnah, This paper focuses on the need for Muslims to maintain health by returning to the Qur'an and Sunnah through the Living Quran and sunnah as the cornerstone of a holistic healthy lifestyle. As a Muslim, it is natural to always practice what is in the Quran and sunnah as a guide for Muslims. A healthy lifestyle according to the Qur'an has also been exemplified by the prophet Muhammad SAW. Because Allah has given Islam handle that affirms the science of health, healthy living, treatment, healthy diet and drinking, and controlling physical and mental stress.  This is reflected in the scriptures as well as the teachings exemplified by the Prophet.